Social Status Retention in the Beyond: the Phobia of Man - Gideon Imoke Emeng (Borong Newinera Publisher, 2021)
Religions include the participation of a community of people who have a common spiritual belief system. It is possible to connect one's own spiritual views with those of others via different religious activities. As a result of social interaction, personal ideas may be shaped and deepened. Both religious ideas and human transpersonal experiences may convey the core of human existence. Religious ideas about life after death may affect how individuals conduct their lives in the here and now. This paper argues that human beings have the inborn drive for statuses. All religions of the world placed serious priority on them, so much: in the ranking of adherents and in the hereafter. Other social institutions see the necessity in statuses placements to enhance productivity, efficiency, proficiency, and profitability. Man in his imagination and realization of this, concludes that the right place to acquire the status is here on earth as the springboard to that of the beyond. He gets it first and this will be maintained in the beyond. By the beyond here we mean abodes after the earthly life. Christianity calls them paradise and hell, likewise Islam and Buddhism describe it as Nirvana. African Traditional Religion mentioned it as the home of the ancestors and the dead. Hinduism has its own as the several reincarnations where the individual soul strives to unite with the supreme Reality also called Brahman. This paper investigates Social Status in the Beyond.